2011
DOI: 10.4028/www.scientific.net/amr.299-300.739
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Microwave-Absorbing Properties of Al<sub>2</sub>O<sub>3</sub> Coated Polyhedral Fe Nanocapsules Prepared by Arc-Discharge Method

Abstract: Al2O3coated polyhedral Fe nanocapsules were prepared by arc-discharging a Fe-Al(8at%Al) alloy. High-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy, and network analyzer were employed to investigate the microstructures, compositions and electromagnetic properties (2-18GHz). The reflection loss R(dB) of the nanocapsules reaches to -50.5dB at 7.9GHz with a 3mm thickness, and EM absorption properties(RL<-20dB) in the 5.2~16.1GHz range with thickness range of 1.67-4.7mm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Al 2 O 3 coated polyhedral Fe nanocapsules were prepared by arc-discharging a Fe-Al (8 atom% Al) alloy. 110 In addition, mobilization and deposition of iron nano and sub-micrometer particles (INSMP) in a porous medium were investigated using a water-saturated glass micromodel. 111 It was shown that there were dense aggregations at the pores as the concentration of INSMP increased.…”
Section: Coated and Supported Iron Nanoparticlesmentioning
confidence: 99%
“…Al 2 O 3 coated polyhedral Fe nanocapsules were prepared by arc-discharging a Fe-Al (8 atom% Al) alloy. 110 In addition, mobilization and deposition of iron nano and sub-micrometer particles (INSMP) in a porous medium were investigated using a water-saturated glass micromodel. 111 It was shown that there were dense aggregations at the pores as the concentration of INSMP increased.…”
Section: Coated and Supported Iron Nanoparticlesmentioning
confidence: 99%
“…both dielectric and magnetic component is a wellconsidered topic in the field of EMI shielding and RAMs [13][14][15][16][17][18]. As the electromagnetic radiation has both dielectric and magnetic component, so it is obvious that both dielectric and magnetic material is effective for the absorption of microwave radiation.…”
mentioning
confidence: 99%
“…Similar to the permittivity curves, the tanδ ε of the Ni@C A nanocapsules exhibits red shift and tanδ µ stands for magnetic loss ability. Generally speaking, the magnetic loss is mainly composed of domain loss, hysteresis loss, eddy current loss and natural resonance loss [3][4][5][6][7][8][9][10][11][12][13]. The magnetic field in the EM wave is too weak to reduce hysteresis; therefore, the hysteresis loss should not be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocapsules-in which the magnetic nanostructure works as a core and the dielectric material acts as a shell-can effec tively enhance thermal stability, improve the electron trans port properties, optimize EM absorption performance, and colligate the magnetic characteristics of the integral materials [8]. Compared with oxides (SiO 2 , ZnO, CuO and Al 2 O 3 ) and conductive polymer, carbonaceous materials have proved to be potential candidates for EM absorbers, due to their high performance compared to cost, low density, good thermal sta bility and excellent corrosion resistance [8][9][10][11][12][13]. Among the carbonaceous candidates, onionlike carbon (OLC) is com posed of a concentric graphite layer with interplane distance of 0.34 nm.…”
Section: Introductionmentioning
confidence: 99%